Horizon Scan on the Benefits of Ocean Seasonal Forecasting in a Future of Increasing Marine Heatwaves for Aotearoa New Zealand - Stevens, Craig L.; Spillman, Claire M.; Behrens, Erik; Broekhuizen, Niall; Holland, Paula; Matthews, Yvonne; Noll, Ben; O'Callaghan, Joanne M.; Rampal, Neelesh; Smith, Robert Owain; Soltanzadeh, Iman; Tait, Leigh W.; et al. (Frontiers in Climate, 2022)
With climate heating, Aotearoa New Zealand is expected to experience more marine heatwaves (MHW) in the coming decades. These extreme events are already impacting the island nation’s marine and coastal environments and marine industries at a variety of scales. There will potentially be substantial benefits in developing an early warning system - specifically ocean seasonal forecast tools. This near-term 2030 horizon scan reviews studies supporting the development of this capability and notes work needed to enable stakeholders to benefit from this knowledge. Review findings congregate around six themes; (1) MHW impacts, (2) mechanistic understanding, (3) observational basis, (4) seasonal forecast tools, (5) supporting Te Tiriti (The Treaty of Waitangi) and Māori aspirations, and (6) end-user engagement. The primary recommendation is a cross-institutional, cross-sector MHW Taskforce that would address, in a coordinated and effective fashion, the real, multi-faceted challenges associated with the committed pathway of warming. A range of sub-recommendations follow that connect with the United Nations Ocean Decade initiative.